Probabilistic Circuit Architecture Using Statistical Learning - Amir Faiz Bin Ab Malik, Amir Faiz (2010)

(untitled)
The main achievement of this project is the generalization of probabilistic circuit architecture. In other words, in mapping MRF into CMOS circuitry, one must fulfill two requirements; first bistable storage element for each logic state and second feedback network for belief propagation.